Directed motivational currents: A systematic review - Jahedizadeh, Safoura; Al-Hoorie, Ali H. (Studies in Second Language Learning and Teaching, 2021)
Directed motivational currents, unique and intense goal-directed motivational surges lasting over a period of time, have received increasing attention recently. This article reports the first systematic review of this phenomenon. A total of 21 reports appearing between 2013 and 2020 were included in the analysis. The results show that the majority of empirical reports were small-scale qualitative studies (median = 18 participants). The evidence on the three characteristics proposed as necessary and/or distinguishing conditions of directed motivational currents (vision, salient facilitative structure, and positive affect) is inconclusive due to the presence of directed motivational currents cases not exhibiting these features, and the absence of direct comparative analyses with non-directed motivational currents cases. A few intervention studies (N = 4) were conducted, but their results are also inconclusive due to a number of methodological limitations. Contrary to the claim that directed motivational current experiences are the “optimal form” of motivation, the results additionally showed that these experiences could lead to intense stress, anxiety, depression, sleeplessness, and panic attacks, thereby raising ethical concerns about deliberately inducing directed motivational currents in learners. We conclude that, although the concept of directed motivational currents is promising, more research is needed to reach a better understanding of its potential. We end this article by suggesting directions for future research into directed motivational currents, including renaming them as sustained flow.